2012
DOI: 10.3390/cryst2020327
|View full text |Cite
|
Sign up to set email alerts
|

Halogen Bonding Interactions in DDQ Charge Transfer Salts with Iodinated TTFs

Abstract: Oxidation of 3,4-ethylenedithio-3'-iodo-tetrathiafulvalene (EDT-TTF-I) and 3,4-ethylenedithio-3',4'-diiodo-tetrathiafulvalene (EDT-TTF-I 2 ) with DDQ afforded two different salts formulated as (EDT-TTF-I)(DDQ) and (EDT-TTF-I 2 ) 2 (DDQ)·(CH 3 CN), both characterized with a full charge transfer to the DDQ acceptor moiety and by short and linear halogen bonding interactions between the iodine atom as halogen bond donor, and the carbonyl oxygen or the nitrile nitrogen atoms of reduced DDQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…3.60 Å (Figure ). An X-ray charge density study by Lecomte et al revealed a partial ionic character: charge of Cl 4 Q is −0.4 e and of TTF is +0.4 e. Over the last few decades, quite a few similar compounds were prepared by using differently substituted derivatives of TTF and the quinone. …”
Section: Strong Stacking Interactions: Multicentric Covalent Bondingmentioning
confidence: 99%
“…3.60 Å (Figure ). An X-ray charge density study by Lecomte et al revealed a partial ionic character: charge of Cl 4 Q is −0.4 e and of TTF is +0.4 e. Over the last few decades, quite a few similar compounds were prepared by using differently substituted derivatives of TTF and the quinone. …”
Section: Strong Stacking Interactions: Multicentric Covalent Bondingmentioning
confidence: 99%
“…It also indicates that it is essentially the negative charge of the TCNQF À 4 radical anion which contributes strongly to the halogen-bond strength, while the I atoms are only weakly activated upon TTF oxidation. This feature was already noted in the charge-transfer salts of the monoiodio TTF derivative, EDT-TTF-I (Lieffrig, Jeannin, Guizouarn et al, 2012;Lieffrig, Jeannin, Shin et al, 2012), The strengthening of the halogen bond in such systems when turning from neutral to ionic is therefore essentially attributable to the negative charge which develops on the halogenbond acceptor, here the nitrile substituent of TCNQF 4 .…”
Section: The Halogen-bond Interactionmentioning
confidence: 62%
“…In the present work, we wanted to suppress this halogen bond/hydrogen bond competition and accordingly concentrated on the analogous diiodotetrathiafulvalene derivative, namely EDT-TTF-I 2 . Because of the presence of two electronwithdrawing I atoms, EDT-TTF-I 2 oxidizes at a rather high potential (0.57 V versus SCE; SCE = saturated calomel electrode), and only a few charge-transfer salts have been described to date, for example with the strong electron acceptor 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ; Lieffrig, Jeannin, Shin et al, 2012), although many cation radical salts were obtained by electrochemical oxidation (electrocrystallization; Domercq et al, 2001;Devic et al, 2002Devic et al, , 2003Alberola et al, 2008;Fourmigué & Auban-Senzier, 2008;Shin et al, 2011). In the DDQ charge-transfer salt formulated as (EDT-TTF-I 2 ) 2 (DDQ), halogen-bonding interactions were observed toward both the O atom of the carbonyl and the N atom of the nitrile groups of reduced DDQ.…”
Section: Introductionmentioning
confidence: 99%
“…In going from DDQ to DDQ À , the negative atomic charges at the sites (C 3 , C 6 ), (Cl 7 , C l8 ) and (C 11 , C 12 ) are increased by 0.18, 0.11 and 0.12 a. u, respectively, whereas at the atomic sites (C 1 , C 2 ), (C 4 , C 5 found to vary due to transition of an electron from the DDQ with A 1 symmetry of electronic wavefunction to its first excited state with B 2 symmetry of electronic wavefunction. On the redistribution of charge in DDQ ⁄ , the atomic sites (C 1 , C 2 ), (C 3 , C 6 ) and (N 13 , N 14 ) gain negative charge whereas the atomic sites (C 4 , C 5 ) and (O 9 , O 10 ) loose negative charges.…”
Section: Charge Distributionmentioning
confidence: 96%
“…Halogen bonding interactions were also explored in charge-transfer salts [2][3][4]. According to Lieffrig et al [5] 2,3-dichloro-5,6-dicyanobenzoquinone (DDQ) acts as a powerful oxidant toward iodinated TTFs and the formation of novel charge-transfer salts with original halogen bonding patterns. DDQ is not only a strong oxidant but also it offers potentially three different halogen bonding acceptor sites, the carbonyl oxygen atoms, the nitrile nitrogen atoms and the chlorine atoms.…”
Section: Introductionmentioning
confidence: 99%